2007
DOI: 10.5153/sro.1588
|View full text |Cite
|
Sign up to set email alerts
|

Is Social Mobility an Echo of Educational Mobility? Parents’ Educations and Occupations and Their Children's Occupational Attainment

Abstract: Biographical noteRichard Lampard is a Senior Lecturer in the Department of Sociology at the University of Warwick. His current research interests include social and educational mobility, the impact of family structure on educational outcomes, the formerly partnered and repartnering, and various other aspects of union formation and dissolution. Department of Sociology

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…[ Tables 1-2 Thus, like Lampard (2007a), this article indicates a key role for parental education in the intergenerational transmission of social position. However, the small difference in fit between Models 6 and 8 (see Table 2) indicates a relatively small effect specific to parental class; both this effect and the overall impact of parental class on salariat attainment are markedly less substantial than in an earlier study (Lampard, 2007a: Table 2).…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…[ Tables 1-2 Thus, like Lampard (2007a), this article indicates a key role for parental education in the intergenerational transmission of social position. However, the small difference in fit between Models 6 and 8 (see Table 2) indicates a relatively small effect specific to parental class; both this effect and the overall impact of parental class on salariat attainment are markedly less substantial than in an earlier study (Lampard, 2007a: Table 2).…”
mentioning
confidence: 83%
“…Analyses of intergenerational class mobility in Britain (e.g. Goldthorpe and Mills, 2008;Kuha and Goldthorpe, 2010) still tend to focus on father's occupation or the 'dominant' parental occupation (Erikson, 1984); however, internationally, authors examining occupational outcomes have highlighted the desirability of taking into account both parents' characteristics (Lampard, 2007a;Schoon, 2008;Beller, 2009;Marks, 2009). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parental education correlates with several other factors such as income, occupation, culture and social resources that matter in a life-cycle perspective. Lampard's (2007) examination of the direct and indirect effects of parents' education and social classes on children's occupational attainment in a British Household Panel Survey (BHPS) has shown that parental education plays a substantial role in the inter-generational transmission of advantage, and has indicated that part (but not all) of the relationship between class origin and occupational attainment can be explained in terms of the inter-generational transmission of cultural capital. Data from the Columbia County Longitudinal Study have revealed a strong relationship between parents' educational level and children's occupation.…”
Section: Discussionmentioning
confidence: 99%
“…A number of social, cultural and economic variables have been identified that associate with movement between social classes, and IQ, educational level as well as childhood social background have all been implicated (Jaeger & Holm, 2003;Nettle, 2003;Richards & Sacker, 2003;Deary et al, 2005;Lampard, 2007;Wolniak et al, 2008;Johnson et al, 2010;von Stumm et al, 2010;Forrest et al, 2011;Sorjonen et al, 2011). In general, the evidence suggests that childhood intelligence, social class of origin and educational qualifications predict status attainment in adulthood.…”
Section: Introductionmentioning
confidence: 99%